DOI: 10.31274/etd-180810-2469
|View full text |Cite
|
Sign up to set email alerts
|

Training methods and topics for hospitality employees with disabilities: Managers' attitudes and perceived knowledge

Abstract: People with disabilities continue to be discriminated against. Training is an important human resource management function that can increase productivity in any organization. This study aimed to assess current training topics and methods used with employees with disabilities, as well as managers' attitudes about people with disabilities, in hotels and restaurants in the United States. Interviews and questionnaires were used for data collection. This study provides information for hospitality industry managers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 25 publications
0
9
1
Order By: Relevance
“…The data collected from the field were coded after which were and mentoring (44%). In contrast to the findings of this study, a study by Paez [20] found that the three training methods most commonly reported by the employees were on the job-training (97%), demonstrations (76%) and self-guided (56%). Also, Harrison [21] found on-the-job training to be one of the training methods most commonly used in the food service industry.…”
Section: Procedures For Data Presentation and Analysiscontrasting
confidence: 99%
“…The data collected from the field were coded after which were and mentoring (44%). In contrast to the findings of this study, a study by Paez [20] found that the three training methods most commonly reported by the employees were on the job-training (97%), demonstrations (76%) and self-guided (56%). Also, Harrison [21] found on-the-job training to be one of the training methods most commonly used in the food service industry.…”
Section: Procedures For Data Presentation and Analysiscontrasting
confidence: 99%
“…Other factors, such as "making others uncomfortable" and "harder to adopt new methods," do not comprise the components of each factor as was stated. Paez [52] and Sharma et al [53], extended Chi and Qu's [49] questionnaire. Similarly to Chi and Qu [49], they, too, did not perform construct validity of their scale.…”
Section: Measurementsmentioning
confidence: 99%
“…In a survey, the investigator examines those phenomena which exist in the universe independent of his action". Originally, the employer attitude assessment questionnaire developed by Chi and Qu (2003), and same tested scale was again revised and utilized by Paez (2010). Both studies were conducted in the USA but in different geographical locations.…”
Section: Methodsmentioning
confidence: 99%
“…Email was sent to the authors of both studies to obtain approval to adopt their questionnaires for this current study. Below table 3 provide brief overview of previous instrument of Paez (2010), and revised instrument for the better understanding.…”
Section: Methodsmentioning
confidence: 99%